Propaganda in revolutionary Ukraine : leaflets, pamphlets, and cartoons, 1917-1922 - Velychenko, Stephen (University of Toronto Press, 2019)
"Propaganda in Revolutionary Ukraine is a survey of domestic governmental and party printed propaganda in revolutionary Ukraine. It is based on an illustrative sample of leaflets, pamphlets, and cartoons published by different parties under the Central Rada, the left-wings of the Ukrainian Socialist Revolutionary Party, the Ukrainian Social Democratic and Labour Party, Ukraine's Bolsheviks, and anti-Bolshevik warlords. The book includes over 300 reproductions, and describes the infrastructure that underlay the production and dissemination of printed texts. It summarizes the messages in printed text propaganda and argues that in the war of words neither Ukrainian failure nor Bolshevik success should be exaggerated. Each side managed to sway opinion in its favor in specific places at specific times."--